The Influence of Net Profit Margin, Operating Cash Flow, Trade Volume, and Intellectual Capital on Firm Value in Infrastructure Sector Companies Listed on the Indonesian Stock Exchange - Dinda Amalia Putri; Lina Budiarti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the effect of Net Profit Margin (NPM), Operating Cash Flow (OCF), Trading Volume, and Intellectual Capital (IC) on Firm Value in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The approach used in this study is quantitative with secondary data obtained from annual financial reports. The population consists of 69 infrastructure companies listed on the IDX, with 33 companies selected through purposive sampling. The analysis was carried out using IBM SPSS 26. The results showed that NPM, OCF, Trading Volume, and IC have a significant positive effect on Firm Value, with a coefficient of determination (R²) of 43.7%, the remaining 56.3% is influenced by other variables not examined in this study. Based on the F test results, it shows that the NPM, OCF, Trading Volume, and IC variables simultaneously affect the Firm Value. Based on the t test results, it shows that the NPM, OCF, Trading Volume, and IC variables partially affect the Firm Value. This finding highlights the importance of financial factors and intangible factors, such as Intellectual Capital, in determining the market value of companies in the infrastructure sector. For investors, these variables are very important in assessing potential investment opportunities. Future research can extend the sample period to include more years and explore additional financial indicators to gain a more comprehensive understanding of the factors that influence firm value. This will provide stronger insights into long-term investment strategies in the infrastructure sector.